"Quality vs quantity": Improved shot prediction in soccer using strategic features from spatiotemporal data - Lucey, P.; Bialkowski, A.; Monfort, M.; Carr, P.; Matthews, I. (MIT Sloan Sports Analytics Conference 2015, 2015)
In this paper, we present a method which accurately estimates the likelihood of chances in soccer using strategic features from an entire season of player and ball tracking data taken from a professional league. From the data, we analyzed the spatiotemporal patterns of the ten-second window of play before a shot for nearly 10,000 shots. From our analysis, we found that not only is the game phase important (i.e., corner, free-kick, open-play, counter attack etc.), the strategic features such as defender proximity, interaction of surrounding players, speed of play, coupled with the shot location play an impact on determining the likelihood of a team scoring a goal. Using our spatiotemporal strategic features, we can accurately measure the likelihood of each shot. We use this analysis to quantify the efficiency of each team and their strategy.